A new species of the genus Sonotetranychus (Acari: Tetranychidae) from New Zealand - Yi, Tian-Ci; Zhang, Zhi-Qiang (Zootaxa, 2013)
The genus Sonotetranychus consisted of seven species prior to this study. Sonotetranychus menziesii sp. nov., collected on Nothofagus menziesii and N. fusca from New Zealand, is described based on females, protonymphs, deutonymphs and a male. An updated key to the species of Sonotetranychus is provided.